German corruption cases reflected in criminal files: individual or organizational deviance? - Dölling, Dieter; Hustus, Ludmila (Organizational crime, 2023)
This article deals with corruption offenses committed by employees of business companies. It examines the question of the extent to which these offenses are individual or organizational deviance. Results of an analysis of German criminal files are presented. The findings refer to characteristics of the offenses and the persons convicted. Corruption delinquency shows considerable intensity in the majority of cases. Most of the offenders held high-level positions in the company. It was found that individual and organizational delinquency can overlap.
Gesehen am 11.05.2023